Igreja Católica e mundo do trabalho: entre aproximações político-pastorais e rupturas socioeclesiais, o itinerário da Igreja do Brasil junto à classe trabalhadora. - Silva Filho, Valmir Assis da (2021)
This study analyzes the paths traced by the Catholic Church in Brazil in its relationship with the world of work, having as a reference the political/pastoral trajectory of the Catholic Worker Action/Christian Workers Movement - ACO/MTC and its challenges in the dialogue with the Church Catholic. The work is structured in a qualitative approach and was carried out in four stages: Bibliographic and Documentary Research; Fieldwork - participant research; Interviews and Testimonies and Data Processing. The bibliographic analysis went through listing and summarizing the chosen works. The field work was carried out from the observation and registration in a field diary of the activities of the Archdiocese of Olinda and Recife and of the MTC, such as Regional and National Seminars, Working Class Weeks, Public Vigils, in addition to meetings of the base teams. During this phase of the work, it was possible to identify the elements for the training of the interviewees. Subsequently, the interviews were conducted and transcribed. The analysis and treatment of data was carried out with a qualitative approach, aimed at offering a better understanding of the social phenomenon object of this study. The analysis of conflicts, approaches, impasses and possibilities in the reconstruction of workers' pastoral in Brazil brought as main considerations the following: The realities where the pastorals and movements of the world of work are inserted are diverse, in such a way that, while some Local churches are beginning to animate a process of pastoral insertion, others do not even promote the protagonism of lay men and women. In this same sense, the clericalization and denial of post-conciliar theology has been configured as impasses to the Church's mission among the working class. On the other hand, it is possible to understand pastoral as a whole, which is a prototype of the synodality that the Church proclaims, as one of the ways out so that the institution can give autonomy to lay people, restart a pastoral project among young workers and can speak and be influential in the most significant discussions that affect the Working class.